(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article explores the interaction between macroeconomics and Uzbek philology through the analysis of economic terms used in the media, scientific texts, and public speeches. The author examines how language is used to enhance economic literacy and how philology adapts complex concepts.